2013
DOI: 10.1158/1078-0432.ccr-12-1940
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Grade Is Associated with the Accumulation and Activity of Cells Bearing M2 Monocyte Markers

Abstract: Purpose: This study is directed at identifying the cell source(s) of immunomodulatory cytokines in highgrade gliomas and establishing whether the analysis of associated markers has implications for tumor grading.Experimental Design: Glioma specimens classified as WHO grade II-IV by histopathology were assessed by gene expression analysis and immunohistochemistry to identify the cells producing interleukin (IL)-10, which was confirmed by flow cytometry and factor secretion in culture. Finally, principal compone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 44 publications
9
129
0
1
Order By: Relevance
“…S6). It has been shown that CD68 þ cells increased in high-grade gliomas (48), and that CD68 þ infiltrating microglias/macrophages were involved in gliomagenesis (49). Together, these suggest that CD68 þ microglias/macrophages play a crucial part to maintain/activate GICs in the niche.…”
Section: Discussionmentioning
confidence: 89%
“…S6). It has been shown that CD68 þ cells increased in high-grade gliomas (48), and that CD68 þ infiltrating microglias/macrophages were involved in gliomagenesis (49). Together, these suggest that CD68 þ microglias/macrophages play a crucial part to maintain/activate GICs in the niche.…”
Section: Discussionmentioning
confidence: 89%
“…TAMs acquire immunosuppressive properties and inhibit cytotoxic activity of CD8 + T cells in tumors. 75 A population of CD68-positive immature myeloid cells (called myeloid-derived suppressor cells (MDSCs) that inhibit proliferation and cytokine release by T cells was found to be present in glioma 76 and squamous cell carcinoma tumors. 77 These cells can be produced by the tumor microenvironment from circulating monocytes.…”
Section: Cd68 In Cancermentioning
confidence: 99%
“…18,19 Gliomas have been shown to employ a variety of mechanisms to suppress the immune system, such as downregulation of MHC class I molecules, production of transforming growth factor-b (TGF-b), vascular endothelial growth factor (VEGF), prostaglandin E2, and IL-10, expression of ligands of checkpoint receptors, such as PD-1, and accumulation of immunosuppressive cells, such as myeloidderived suppressor cells (MDSCs), regulatory T cells (Tregs), and tumor-associated macrophages (TAMs). [23][24][25][26][27][28][29][30] It has been previously shown in human samples and experimental GBM models that MDSCs are powerful inhibitors of anti-tumor immune responses. 30,31 Through a variety of mechanisms that inhibit T cell activation and expansion, including the production of arginase and inducible nitric oxide synthase (iNOS), reactive oxygen species and/or reactive nitrogen species (ROS and/or RNS), release of IL-10, expansion of regulatory T cells (Tregs), and inhibition of T cell migration, MDSCs have been shown to promote immunosuppression and tumor progression.…”
Section: Malignant Brain Tumors (Gliomasmentioning
confidence: 99%